SITUS LIANGAN DALAM BINGKAI SEJARAH MATARÄM KUNO - Sugeng Riyanto (Berkala Arkeologi, 2017)
Liangan site â€“ found in 2008 and being researched since 2009 â€“ is an intricate site. At least three type of areas have been unearthed, viz. settlement, agriculture, and Hinduistic worship, which buried in 3 hectares area of Mt. Sindoro volcanic material. Archaeological data and carbon dating have indicated that Liangan site extend between II to XI AD. Thus, the specific historical context of Liangan based on existing archaeological evidences has become a separate issue. Through descriptive-analytical methods, supported by historical sources, it is known that the ancient civilization of Liangan had developed sincepre-Hindu to Ancient MatarÄm periods. To be more specific, the Liangan site can be associated with Rakai Layang Dyah Tlodhong, the king of MatarÄm who reigned from 918 to 928 AD, both indicating that the ancient Liangan settlements were of watak, not wanua.